EVALUATION OF BACTERICIDAL EFFECTIVENESS OF BENZALKONIUM CHLORIDE - K. Imandel; M.B. Shaywaard; F. Mobaraki (Tehran University of Medical Sciences, 1996)
Benzalkonium chloride is a quaternary ammounium Compounds derivative under different names such as Afxhang, Hamoon, Mahan etc, which have great and expanded use in sanitation and medical affairs. Bactericidal activity of these disinfectants was fulfilled according to National Standard Method No.2842 on Staph. Aureus, Sal. Typhimouium and E. coli. This laboratory test showed that, except Mahan that has not bactericidal efficacy on E.coli at concentration 0.4 percent, other disinfectants under the study in concentrations of 0.4, 0.8, 1, 1.2 percent have reliable antibacterial properties, and bacterial resistance to benzalkonium chloride has not occurred yet.